Parallel Processing for Vertex Triple Number Search Processes in Not Different Graph Using Shared Memory Models - Ayuningtyas, Astika (Sekolah Tinggi Teknologi Adisutjipto, 2018)
Parallel processing is an effective strategy for describing large problems in smaller problems, in which computing techniques use two or more computers to perform a task simultaneously by optimizing the resources of existing computer systems. This study uses parallel processing techniques, in which the object of the search is the process of finding the number of triple vertices not represented in the graph. The parallel worker process then divides the workload into each process and distributes it to other threads in the system to solve a problem. The model used in parallel processing is shared memory. This model optimizes the performance of threads on the processor. The experiments carried out make it possible to conclude that the processing speed of a parallel system is influenced by the number of processes and the number of vertices. On a single computer, the larger the process, the shorter the process. The same with the increase in the number of vertices resulting in a longer time.